Pengaruh Fluktuasi Harga & Ketersediaan Bahan Baku Kedelai Terhadap Hasil Produksi Perajin Tempe di Desa Pejaten, Kecamatan Kramatwatu, Kabupaten Serang, Provinsi Banten - R.J. Bladys Sultany Xyalam; Andjar Astuti; Ratna Mega Sari (UM Purwokerto Press, 2023)
Tempeh is a high protein food that is reasonably priced. Capital constraints are a common source of concern in the temporary housing industry, and raw material prices are rising. To avoid losses, many tempeh artisans in Kramatwatu improvise during the tempeh-making process. Production components are inextricably linked in determining a production. The goal of this study was to see how price fluctuations and raw material availability affected tempeh production in Pejaten Village, Kramatwatu District. This research method is known as quantitative research. Simple random sampling was used as the sampling technique. 35 home industries were used as samples in this study. According to the study's findings, price and availability fluctuations in raw materials have a significant impact on the variable results of tempeh production. Furthermore, the results of the concurrent test show that price fluctuations and raw material availability have a significant impact on tempeh production in the Kramatwatu District. The obtained R2 value is 0.888. It can be concluded that price fluctuations and raw material availability have an overall effect of 88.8% on tempeh production yield, with the remaining 11.2 percent influenced by variables not researched.